Problematika Validasi Pajak Oleh Kantor Pajak Pratama Terhadap Akta PPAT - Mohammad Taufan Kumangki (Universitas Islam Indonesia, 2020)
This study aims to examine the problems of tax validation by the Pratama Tax Office on the Deeds of Land Titles Registrar (PPAT). This research uses normative legal study on the principles, norms, rules of statutory regulations, court decisions, agreements and doctrines. The results of this research conclude that the legal consequence of the pending tax validation process on the PPAT Deed Registration is that tax validation is a state administrative task, the absence of validation of the sale and purchase tax results in the inability of sale and purchase registration for the transfer of rights to land to the Land Office. By customary law, the sale and purchase paid in full results in the buyer having obtained the right to the land, but because the sale and purchase certificate has not been registered to the Land Office, the land has not been legally transferred to the Buyer. Furthermore, in order to solve these problems by referring to the problems encountered in practice, the BPHTB tax validation process with the income tax validation at the Pratama Tax Office shows that there is a lack of files submitted or underpayments of previously paid taxes, hence taxpayers personally or through their proxies are requested to amend or complete the missing documents, to be able to re-apply for validation, this takes a long time and PPAT in Manado City has to make a statement of delay on the Sale and Purchase Deed.